2014
DOI: 10.1186/1471-2407-14-14
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the pulmonary artery induced by metastatic gastric carcinoma: a histopathological analysis of 51 autopsy cases

Abstract: BackgroundGastric carcinoma remains the second commonest cause of cancer deaths worldwide. Presence of the carcinoma cell in the pulmonary artery is serious condition that might cause remodeling of the pulmonary artery. The present study conducted detailed histopathological analyses to elucidate how gastric carcinoma cells may affect the structure and hemodynamics of pulmonary arteries.MethodsRemodeling of the pulmonary artery was assessed based on measurements of arterial diameters and stenosis rates from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…To our knowledge, two previous meta-analyses also explored the association of NLR with prognosis of HCC [102103]. Both of them were published in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, two previous meta-analyses also explored the association of NLR with prognosis of HCC [102103]. Both of them were published in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our patient showed an exceptionally low Ki-67 labeling index (3.7%). In addition, several studies on neuroendocrine tumors have reported that bcl-2 or p53 expression might be correlated with malignant behavior [1317, 19, 2327]. However, no studies were found in which investigation was limited to SPC.…”
Section: Discussionmentioning
confidence: 99%
“…STOP CRC has two phases: The first, Phase 1, was a pilot phase [22]. During the pilot phase we developed our EHR tools and tested two interventions in a two FQHC clinics belonging to a single health organization.…”
Section: Methodsmentioning
confidence: 99%
“…Phase 2 is a larger two-arm cluster-randomized study involving 26 FQHC clinics and 8 health organizations. Phase 1 pilot findings showed an overall 37 percentage point increase in CRC screening in intervention, compared to Usual Care (UC), clinics (38% vs. 1% over a 6 month period, based on intention-to-treat analyses) [22]. Here, we describe the Phase 2 study design and protocol.…”
Section: Methodsmentioning
confidence: 99%